Association between statin use and acute pulmonary embolism in intensive care unit patients with sepsis: a retrospective cohort study - Yang, Dengcang; He, Yanyan; Wang, Qianqian; Yu, Yi (Frontiers in Medicine, 2024)
Introduction: Acute pulmonary embolism (APE) is a life-threatening medical condition that is frequently encountered and associated with significant incidence and mortality rates, posing a substantial threat to patients' well-being and quality of life.Sepsis is prominent independent risk factor for the development of APE. Despite recent investigations indicating a reduced APE risk through statin therapy, its impact on patients with sepsis and APE remains unresolved.The Medical Information Mart for Intensive Care (MIMIC)-IV database was utilized to identify patients diagnosed with sepsis and APE, irrespective of statin treatment status, as part of this study. The primary study aim was to assess the risk of APE, which was analyzed using multivariate logistic regression models.The study encompassed a total of 16,633 participants, with an average age of 64.8±16.2 years. Multivariate logistic regression revealed that septic patients receiving statin therapy in the intensive care unit (ICU) exhibited a 33% reduction in the risk of developing APE (OR=0.67, 95% CI: 0.52-0.86, p<0.001). The findings of further analyses, including stratification based on statin usage, dosage, and propensity score matching, consistently reinforced the hypothesis that administering statins to patients with sepsis effectively mitigates their potential APE risk.The results of the study provide compelling evidence in favor of administering statins to septic patients as a prophylactic measure against APE, given that statins may reduce the risk of developing APE, and their anti-APE effect appears to be dose-dependent. Nonetheless, future randomized controlled trials are needed to validate these results.